2009
DOI: 10.2334/josnusd.51.47
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with urgent oral care among adult Tanzanians

Abstract: The aim of this study was to determine patient satisfaction with urgent oral care and to evaluate the association between patient satisfaction and different aspects of such care. A 5-point Likert scale questionnaire on patient satisfaction (score 1 = very dissatisfied; score 5 = very satisfied) was administered to 741 adults. Chi-squared test and logistic regression analysis were used to identify associations between dependent and independent variables. The mean patient satisfaction score was 3.79 (SEM = 0.02)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…These findings are similar to those reported by Okullo et al 2004 (5) among secondary school students in Kampala and Lira in Uganda, among adults in Tanzania (3,18), among adults in Los Angeles, U.S.A (12); and among 23-year olds in Norway (11). In these studies the proportion of respondents who reported being satisfied with oral care ranged from 60% -77%.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These findings are similar to those reported by Okullo et al 2004 (5) among secondary school students in Kampala and Lira in Uganda, among adults in Tanzania (3,18), among adults in Los Angeles, U.S.A (12); and among 23-year olds in Norway (11). In these studies the proportion of respondents who reported being satisfied with oral care ranged from 60% -77%.…”
Section: Discussionsupporting
confidence: 89%
“…The assurance and the high response rate indicated that the findings were reliable. In addition, the items used in the current study had been tested for reliability in Tanzanian settings, and both the re-test and within a scale reliability coefficients were high (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The practice assessment measures (DMS‐BR, SOADC) assessed the dimensions of (i) safety, with measures addressing the use and provision of personal protective equipment and (ii) efficacy, using measures of ability of practice members to work as a team. The patient satisfaction surveys covered a range of dimensions, for example: safety – satisfaction with cleanliness of facilities; effectiveness – satisfaction with treatment received 33 ; patient‐centredness – perception of dentist caring about patient; timeliness – satisfaction with waiting times to see a dentist; efficiency – patient satisfaction of cost and equity – patient perception of dentist acceptance of them as a person.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore studies explored the relationship between patient satisfaction and the quality of care (Van Campen andSixma, 1995, Hutchison et al, 2003) as well as its evolution over time, in different groups of patients and in various health care settings and cultural or geographical contexts (Allan et al 2009;McCabe et al 2008;Piron et al 2008;Kikwilu et al 2009;Lochoro, 2004). Mrayyan in 2006(Mrayyan, 2006, and with the input of Lochoro in 2004and Wolosin in 2005(Wolosin, 2005, the concept of patient satisfaction has moved from a more theoretical essence to a more technical and operational approach.…”
Section: The Concept Of Patient Satisfactionmentioning
confidence: 99%